THE USE OF DAYAK SEBERUANG LANGUAGE IN TEACHING ENGLISH LANGUAGE - Atrianus Toni (Pedagogic Research-Applied Literacy Journal, 2024)
This study explores the application of the Seberuang Dayak language in teaching the English language. The focus is on how this local language can be used as a tool in improving students' understanding and English language skills. The methodology used includes interviews, classroom observations, and qualitative data analysis. The study results show that the use of the Dayak Seberuang language in English teaching helps students understand concepts better, reduces anxiety, and increases learning motivation. These findings suggest that the integration of local languages English curriculum can enrich the learning experience and support the achievement of better outcomes for students. This research provides new insights into the multilingual approach to language education.